Testing Students’ Entrepreneurial Self-Efficacy as an Early Predictor of Entrepreneurial Activities. Evidence From the SEAS Project - Krzysztof Zięba; Jakub Golik (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Over the last forty years, since Bandura (1977) introduced the concept of selfefcacy, there have been a constantly growing number of research publicatons using this concept. Its early development resulted in the creaton of a new construct of entrepreneurial self-efcacy (ESE) proposed for the frst tme by (Chen et al. 1998). Since then, many diﬀerent groups of research concerning ESE have emerged - one of them is the study of ESE of students. With regard to this partcular group, a recent tendency to study ESE in a pre-post setng can be notced i.a. Karlsson, Moberg (2013), Shinnar, Hsu, Powell (2014), Ismail, Zain, Zulihar (2015). Due to the increasing interest in entrepreneurial self-efcacy research and the need to fll the gap in the literature with regard to European post-communist countries (and partcularly – Poland) (Drnovsek, Wincent, Cardon, 2010), in this paper we present a brief overview of ESE research and pose the queston whether ESE of Polish students can serve as an early predictor of their subsequent entrepreneurial actvites, potentally leading them to nascent entrepreneurship. The research material was collected from the SEAS (Survey on Entrepreneurial Attudes of Students) Project carried out at the Faculty of Management and Economics, Gdańsk University of Technology. The research sample was composed of 72 students - ESE was measured in a pre-post setng using a single item based on a fve-point Likert scale. One of the research conclusions is that ESE manifested by student-beginners seems to inﬂuence their later entrepreneurial behavior in a statstcally signifcant way - potentally making ESE a valuable early predictor of future entrepreneurial actvites. In the concluding part of the study, limitatons are discussed and future study developments are indicated.